2019
DOI: 10.1039/c9ra01203f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis ofN-aryl β-amino acid derivativesviaCu(ii)-catalyzed asymmetric 1,4-reduction in air

Abstract: Non-precious metal copper-catalyzed asymmetric 1,4-hydrosilylation of β-aryl or β-alkyl-substituted N-aryl β-enamino esters proceeded in air in high yields and excellent enantioselectivities (26 examples, 90–98% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…For example, Wu and co-workers showed that both β-amido and anilido substituents give access to different chiral βamino esters 13 in generally high yields and enantioselectivity (Figure 6). [48][49][50] The best ligands for this class of substrates were shown to be L7 or L10, depending on the Nsubstitution. Similarly, the Buchwald group showed in 2004 that the reduction of β-azaheterocyclic unsaturated esters is feasible using L6 (Figure 6).…”
Section: αβ-Unsaturated Esters Amides and Acidsmentioning
confidence: 99%
“…For example, Wu and co-workers showed that both β-amido and anilido substituents give access to different chiral βamino esters 13 in generally high yields and enantioselectivity (Figure 6). [48][49][50] The best ligands for this class of substrates were shown to be L7 or L10, depending on the Nsubstitution. Similarly, the Buchwald group showed in 2004 that the reduction of β-azaheterocyclic unsaturated esters is feasible using L6 (Figure 6).…”
Section: αβ-Unsaturated Esters Amides and Acidsmentioning
confidence: 99%
“…[44] The development of synthetic approaches to β-amino ketones, β-amino sulfones, β-amino acids and their derivatives (esters and nitriles) bearing arylamine moiety has a special importance because of their numerous applications to divers functional materials, drugs and analogs of natural products. [45,46] Arylamines are generally viewed as relatively poor nucleophiles toward electrophiles, including Michael acceptors, especially ones bearing internal carbon-carbon double bond. Therefore, it is reasonable to assume that for success, their reactions with electron-deficient alkenes should require an additive (catalyst) that can increase their reactivity.…”
Section: Non-catalyzed Conjugate Nucleophilic Addition Of Aminesmentioning
confidence: 99%
“…Wu et al presented an interesting approach to exploiting prochiral precursors to produce β-amino acid esters by developing enantioselective conjugate reductions of (βarylamino)-β-alkyl or β-arylacrylates. 114 The reaction was accomplished with a PMHS-derived CuH-catalysis system and (S)-SEGPHOS (S)-L2. Various alkyl and aryl-substituted substrates produced excellent results (Scheme 113 and Scheme 114).…”
Section: Asymmetric Reduction Of αβ-Unsaturatedmentioning
confidence: 99%